Pollution, Ability, and Gender-Specific Responses to Shocks - Teresa Molina (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2019)
This paper explores how labor market conditions drive gender differences in the human capital decisions of men and women, focusing on how their schooling decisions respond to an exogenous change in cognitive ability. Using data from Mexico, I begin by documenting that in utero exposure to air pollution leads to lower cognitive ability in adulthood for both men and women. I then explore how male and female schooling decisions respond differentially to this cognitive shock: for women only, pollution exposure leads to reduced educational attainment and income. I show that two labor market features are fully responsible for this gender difference: (1) women sort into white-collar occupations at higher rates, and (2) schooling and ability are more complementary in white-collar than blue-collar occupations.
Keywords: I26; Q53; J24; 330; gender; occupational choice; early life; pollution; education; Mexico